Evaluation of the Safety of Whole Milk in Wolaita Zone, Southern Ethiopia (Global Journal of Science Frontier Research, 2016)
A study was conducted to evaluate the quality and compositions of whole raw cow milk from farm(producers handling levels) to table(collectors handling levels) in Wolaita Zone of Soddo Town and Kokate Kebele. A total of thirty milk samples were collected from 30 dairy farmers (producers) at Kokate kebele who sold their milk at Soddo town and twenty five whole milk samples were collected from 25 café , s and hotels (collectors) at Soddo town using clean test tube. The major components(fat, lactose, SNF, protein, salt and water) and physical properties(density, temperature and freezing point) of milk samples were immediately analyzed using milk analyzer machine. The result showed that the mean content of lactose, SNF, protein, salt, density and Freezing point of milk samples at producers handling conditions (4.71± 0.08, 8.40±0.13, 3.04± 0.05, 0.73± 0.01, 27.29± 0.56 and 0.60± 0.01) were significantly higher than that of collectors levels (3.74±0.15, 6.73±0.26, 2.41±0.10, 0.58±0.02, 21.34±0.93 and 0.43±0.02).
Keywords: safety; milk; producers; collectors